2014
DOI: 10.1002/asna.201412069
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese comet observation in AD 773 January

Abstract: The strong 14C increase in the year AD 774/5 detected in one German and two Japanese trees was recently suggested to have been caused by an impact of a comet onto Earth and a deposition of large amounts of 14C into the atmosphere (Liu et al. 2014). The authors supported their claim using a report of a historic Chinese observation of a comet ostensibly colliding with Earth's atmosphere in AD 773 January. We show here that the Chinese text presented by those authors is not an original historic text, but that it … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…However, as we have shown already (Chapman et al 2014), this claim was not correct for several reasons:…”
Section: The Comet Of Ad 773 Januarymentioning
confidence: 64%
See 3 more Smart Citations
“…However, as we have shown already (Chapman et al 2014), this claim was not correct for several reasons:…”
Section: The Comet Of Ad 773 Januarymentioning
confidence: 64%
“…The two Chinese comet reports in the mid AD 770s also do not relate to the 14 C increase: The comet of January 773 did not collide with the Earth's atmosphere (Chapman et al 2014), and the comet reported for AD 776 was actually observed nine years earlier (Sect. 5.2).…”
Section: The Possible Korean Comet In Ad 776 Junementioning
confidence: 94%
See 2 more Smart Citations
“…www.an-journal.org Chapman et al (2014) show that the original Chinese texts about this comet just report about a very normal comet observed in China on or since AD 773 Jan 17 (also observed in Japan on or since Jan 20), and that the material presented in Liu et al (2014) is misleading: There is no evidence for a collision of a comet with Earth.…”
Section: Possible Causesmentioning
confidence: 86%